A COMMUNITY SINERGITY IN COMMUNITY-BASED COMMUNITY ECONOMIC EMPOWERMENT (CBT): STUDY OF ECOWISATA BATU JUBANG, MUMBULSARI, JEMBER - Bagus Prayogi, Khorul Hadi Asy’ari, Ainul Churria almalachim (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2020)
Tourism is not a primary human activity, but only a complement in human life. Nevertheless, tourism activities cannot be ignored. Some studies say that tourism can reduce stress after being tired of doing daily activities such as work, school, and so on. Now the concept of developing a lot of tourism one of which is ecotourism. The concept promoted by ecotourism itself is a combination of nature and cultural preservation and with community participation, ecotourism efforts are increasingly loved by many groups. One of the ecotourism in Indonesia is Batu Jubang ecotourism in Jember, East Java. Batu jubang ecotourism raises the concept of Community Based Tourism (CBT) in order to advance and prosper the lives of the people around Batu Jubang ecotourism. This research raises the theme of Community Synergy in Community Based Tourism (CBT)-based Economic Empowerment: Study on Batu Lubang Ecotourism, Mumbulsari, Jember. That way, the focus of this research is first, how is the concept of Community Based Tourism in a gully? second, how far is the use of Community Based Tourism in Batu Jubang? Third, what is the impact of the use of Community Based Tourism in pits? by using descriptive analysis methods to answer the concept of using Community Based Tourism while using community based tourism and the impact of using community based tourism are explained using a qualitative approach. The results of this study are first, knowing the concept of Community Based Tourism. Second, knowing the extent of the use of Community Based Tourism in the pit. third, knowing how the impact of using Community Based Tourism in Batu Jubang.